2005
DOI: 10.1111/j.1600-6143.2005.01063.x
|View full text |Cite|
|
Sign up to set email alerts
|

Three‐Year Efficacy and Safety Results from a Study of Everolimus Versus Mycophenolate Mofetil in de novo Renal Transplant Patients

Abstract: Everolimus 1.5 or 3 mg/day was compared with mycophenolate mofetil (MMF) 2 g/day in a randomized, multicenter 36-month trial in de novo renal allograft recipients (n = 588) receiving cyclosporine microemulsion (CsA) and corticosteroids. The study was doubleblind until all patients had completed 12 months, then open-label. By 36 months, graft loss occurred in 7.2, 16.7 and 10.7% of patients in the everolimus 1.5, 3 mg/day, and MMF groups, respectively (p = 0.0048 for everolimus 1.5 mg/day vs. 3 mg/day); efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
166
0
16

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(200 citation statements)
references
References 33 publications
17
166
0
16
Order By: Relevance
“…7) A lower incidence rate for CMV infection was also observed in a randomized trial of renal transplant recipients treated with EVL compared with MMF. 9,10) Although there is little molecular evidence supporting a relationship between EVL and CMV, Johnson and colleagues have reported that CMV up-regulates the phosphatidylinositol 3-kinase (PI3-K) pathway and inhibition of PI3-K activity in turn inhibits viral replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7) A lower incidence rate for CMV infection was also observed in a randomized trial of renal transplant recipients treated with EVL compared with MMF. 9,10) Although there is little molecular evidence supporting a relationship between EVL and CMV, Johnson and colleagues have reported that CMV up-regulates the phosphatidylinositol 3-kinase (PI3-K) pathway and inhibition of PI3-K activity in turn inhibits viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…7) Meanwhile, everolimus (EVL), which has been approved for HTx patients in Europe and Japan, 8) is also known to reduce the rate of CMV infection. 7,9,10) We here report a recipient with positive CMV antigenemia, neutropenia, and renal impairment, whose neutrophil count and renal function recovered by conversion from MMF to EVL and reduction of the tacrolimus dose. Assay for CMV antigenemia was continuously negative in spite of VGC discontinuation in this case.…”
Section: Ytomegalovirus (Cmv) Infection Remains a Major Fatalmentioning
confidence: 99%
“…First, there is the observation that both sirolimus and everolimus increase chronic nephrotoxicity of CNIs, both in rats (272) and in humans (273)(274)(275). This is explained by robust evidence that these mTOR inhibitors interact with cyclosporine excretion in tubular epithelial cells through competition for P-glycoprotein (276,277), and hence lead to accumulation of cyclosporine in these cells.…”
Section: Local Renal Exposure To Cyclosporine and Tacrolimusmentioning
confidence: 99%
“…Immunosuppressive treatment was continued with prednisone (7.5 mg/day), SRL and tacrolimus and the patient remained without edema as also with a good clinical condition. Edema is considered as a drug class effect in patients treated with mTOR inhibitors, either SRL or everolimus [6]. It could be argued that edema is a very common complication in renal allograft recipients whatever immunosuppressive treatment is taken [4].…”
Section: Casementioning
confidence: 99%